The Effect of International Travel Arrivals on the New HIV Infections in 15–49 Years Aged Group Among 109 Countries or Territories From 2000 to 2018 - Du, Min; Yuan, Jie; Jing, Wenzhan; Liu, Min; Liu, Jue (Frontiers in Public Health, 2022)
Objective The prevalent international travel may have an impact on new HIV infections, but related studies were lacking. We aimed to explore the association between international travel arrivals and new HIV infections in 15–49 years aged group from 2000 to 2018, to make tailored implications for HIV prevention. Methods We obtained the data of new HIV infections from the Joint United Nations Programme on HIV/AIDS and international travel arrivals from the World Bank. Correlation analysis was used to explore the relation briefly. Log-linear models were built to analyze the association between international travel arrivals and new HIV infections. Results International travel arrivals were positively correlated with new HIV infections (correlation coefficients: 0.916, p < 0.001). After controlling population density, the median age of the total population (years), socio-demographic index (SDI), travel-related mandatory HIV testing, HIV-related restrictions, and antiretroviral therapy coverage, there were 6.61% (95% CI: 5.73, 7.50; p < 0.001) percentage changes in new HIV infections of 15–49 years aged group associated with a 1 million increase in international travel arrivals. Conclusions Higher international travel arrivals were correlated with new HIV infections in 15–49 years aged group. Therefore, multipronged structural and effective strategies and management should be implemented and strengthened.